Morpho-molecular characterization of fungi associated with seeds of hybrid rice varieties in bangladesh - Liza, Sangida Akter; Shamsi, Shamim; Noman, Md Abdullah Al (Bangladesh Journal of Botany, 2024)
Rice, as the dominant crop in Bangladesh, is vulnerable to various fungal pathogens. Many of these pathogens infect the seeds, which can later transmit diseases and serve as an efficient means for spreading seed-borne pathogens over long distances. In this study, seven hybrid rice varieties, specifically BRRI Hybrid Dhan 101 through BRRI Hybrid Dhan 107, were collected from the Bangladesh Rice Research Institute (BRRI) to detect and identify seed-borne fungi using both morphological and molecular techniques. Fourteen fungal species were isolated from the selected rice varieties using “Tissue planting method” and “Blotter method”, of which 4 fungal isolates were identified by molecular techniques. Molecular characterization of the isolates was conducted based on the sequence information of internal transcribed spacer (ITS) regions. The sequences obtained using the ITS1 and ITS4 primers were compared with those in the NCBI GenBank using BLAST analysis. Hybrid rice is comparatively more advantageous than inbreed rice because of its high yield, shorter plant life, and higher assimilation translocation. Therefore, it is crucial to identify and manage the pathogenic fungi associated with the seeds to ensure good seed quality, which can contribute to improving the economy of Bangladesh. Bangladesh J. Bot. 53(3): 511-518, 2024 (September)